Analysis of learning curve of minimally invasive total knee arthroplasty: A single surgeon's experience with 4017 cases over a 9-year period. Issue 7 (July 2019) - Cheng, Yu-Chi; Wu, Po-Kuei; Chen, Cheng-Fong; Chen, Chao-Ming; Tsai, Shang-Wen; Chang, Ming-Chau; Chen, Wei-Ming
Abstract : Background: To evaluate a single surgeon's experience with minimally invasive total knee arthroplasty (MIS-TKA) and report the 9-year learning curve and trends in clinical outcomes based on assessment of surgical skills, radiographic alignments, and patient's function scores. Methods: This retrospective study included a total of 4107 knees from 3403 patients undergoing bilateral or unilateral MIS-TKA between March 2004 and February 2013. MIS-TKA was performed through a modified mini-midvastus approach. Postsurgical care regime was standardized for all patients. Data of consecutive 3-month intervals were collected and compared for changes of trends in outcomes over time, including tourniquet time, intraoperative complications, radiographic alignment, the Knee Society Score (KSS), and functional scores. Results: Significant increase in the number of cases undergoing MIS-TKA per 3-month interval over the study period was observed. As surgeon's experience increased over time, tourniquet time was decreased from an average of 70 minutes to approximately 35 minutes. A total of 65 (1.68%) intraoperative complications were recorded and the frequencies were in a significant decreasing trend. The rate of malalignment was in a decreasing trend and steady desired alignment (6°) was achieved at the 15th three-month interval. KSS and function scores increased from 87.4 to 91.5 and 92.6 to 96.8, respectively. Conclusion: Although a surgeon may become competent with MIS-TKA and achieved the preliminary learning curve within one year, experience accumulation continuously improved technical proficiency in MIS-TKA. This study confirmed significant improvements in surgical skills, postoperative alignment, and patients' function over time.